Tri Hita Karana Philosophy in the Awig-awig of the Bali Aga Community towards Ecological Citizenship - Tripayana, I Nengah Agus; Bestari, Prayoga; Malihah, Elly; Syaifullah, Syaifullah (Komunitas: International Journal of Indonesian Society and Culture, 2024)
This research seeks to examine the actualization of the Tri Hita Karana philosophy in the awig-awig of Balinese society in realizing ecological citizenship. The research was conducted in Tenganan Pegringsingan village, Karangasem District, Karangasem Regency, Bali. Using qualitative methods. Data collection was carried out through documentation studies. The research results show that the tri hita karana philosophy states in the rules is contained in awig-awig Bali society. The palemahan aspect, namely realizing harmonious relations between humans and nature in realizing ecological citizenship, is implemented in articles 7, 8, 9, 12, 14, 37, 38, 51, 55, 61 which regulate the prohibition on picking fruit, cutting down trees, changing land functions, settlements, agricultural patterns, spatial planning and environmental conservation. The existence of awig-awig is able to realize ecological citizenship based on Tri Hita Karana.